Seni Menyampaikan Perasaan Melalui Lagu Berjudul "Sang Bayu" Karya Hariyadi - Misnawati Misnawati (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study explores the lyrics and creative process behind the song "Sang Bayu" created by Hariyadi . The main focus of the analysis is on the use of language and metaphors in the lyrics that depict the theme of love and romance. The lyrics of this song contain deep expressions of love and use metaphors such as "blowing the wind of love" to express soft and calming feelings. The main theme raised is love and romance, where the lyrics display soft and affectionate feelings. The melody that supports the lyrics also strengthens the romantic and calming atmosphere. This study also includes an interview with Hariyadi, who explains the process of creating this song through musical reflection and experimentation, as well as expressing personal inspiration from the beauty of nature and true love. This study identifies that the combination of poetic language, symbolism, and flowing lyrical structure provides a strong emotional and aesthetic effect.